Organizational responses to multiple logics: Diversity, identity and the professional service firm. (November 2022) - Anderson-Gough, Fiona; Edgley, Carla; Robson, Keith; Sharma, Nina
Abstract: This paper is located within the research problematic of multiple logics with reference to professional service firms (PSFs), and in particular audit firms. Within this multi-logic ("hybrid") and complex organization, we are specifically concerned with the impacts of new institutional logics that reflect social and political movements - in this case diversity legislation - and how these new logics are absorbed and managed within the organizations' structures and practices. Based upon a study of large and medium sized audit firms in the UK, we consider the organizational responses to the demands for improved diversity among firm members, especially the senior elite, in the context of the passing of the Equality Act, 2010, and subsequent legislation which both consolidated and extended UK laws on discrimination. Our study indicates how such organizational sites have value for demonstrating how the conflict between logics shifts its terms of reference. While most of the conflict between logics of commercialism and professionalism has been successfully managed through mechanisms of hybridization, we bring to the fore how the struggles between ideas about merit and diversity in professional evaluation processes and practices are more intractable. Our work contributes to an understanding of both the dependencies ( blending ) and co-existences ( separation ) that can exist between diversity, commercial and professional logics of practice in multi-logic organizations. We further highlight the role of identity scripts that shape how individuals situationally demarcate their identities as they struggle with the demands for diversity that challenge dominant logics.